THE INFLUENCE OF PARENT ATTACHMENT, EXPOSURE OF MEDIA AND PEOPLE TO THE EARLY ADOLESCENT SEX BEHAVIOUR IN THE MIDDLE SCHOOL (SMP) STATE 4 MADYA CITY HIGH CLIFFS IN 2019 - EKA PERMATASARI PURBA; HERIANTO BANGUN (LP2MTBM MAKARIOZ, 2020)
Adolescence is a period of rapid growth and development. it allows adolescence to fall into negative things. One of thenegative things that becomes a teenager's problem is early sexual behavior. The purpose of this study was to determine theeffect of attachments, media exposure and peers on early adolescent sex behaviour in the State High School 4 TebingTinggi in 2019.The type of research was observational analytic research using the cross sectional approach. The populationin this study were 117 students in Tebing Tinggi State Middle School 4. Data analysis in this study used univariate, bivariate,and multivariate analysis. The findings of this study that obtained by old attachments, media exposure and peers had asignificant relationship with early sexual behaviour in adolescents in State Middle School 4 Tebing Tinggi. parentalattachment obtained p <0,05 it means that there is a relationship between parental attachment and early adolescent sexbehaviour, media exposure obtained p <0,05, it means that there is a relationship between media exposure and earlyadolescent sex behavior, peers obtained p <0,05 meaning that there is a relationship between peers with early adolescentsex behavior. Multivariate results obtained that the most dominant media exposure in relation to adolescent sex behaviorwith a value of p <0.05 with Exp (B) 10.381 means that exposure to 10,831 media exposures is likely to engage in earlysexual behavior compared to not exposed to media exposure. It is expected that the school will establish a adolescenceReproductive Health Program to increase adolescent knowledge about risky sexual behavior.